2019
DOI: 10.1111/jphp.13157
|View full text |Cite
|
Sign up to set email alerts
|

Muscone ameliorates diabetic peripheral neuropathy through activating AKT/mTOR signalling pathway

Abstract: Objectives Emerging evidence showed that muscone could improve chronic inflammation after myocardial infarction and protect alcohol‐induced osteonecrosis of the femoral head. However, the function of muscone on diabetic peripheral neuropathy (DPN) is obscure. Methods The neuronal Schwann cell RSC 96 cells were treated with 125 mmol/l glucose to simulate the cells in DPN. The RSC 96 cell viability was detected by cell counting kit‐8. The RSC 96 cell cycle and apoptosis were determined by flow cytometry. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Furthermore, muscone treatment could alleviate memory dysfunction in APP/PS1 mice, reduce Aβ levels, and enhance synaptic plasticity (42). Musk ketone molecules are responsible for the main physiological activity of musk, which can not only resist dementia and fight against cerebral ischemia, but also has low cytotoxicity and a variety of potential health benefits, such as anti-tumor effects, beneficial effects on ischemic heart disease, and the inhibition of diabetic peripheral neuropathy (38,43,44). These effects will help promote cell proliferation and angiogenesis, reduce apoptosis and inflammation, and maintain cell viability, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, muscone treatment could alleviate memory dysfunction in APP/PS1 mice, reduce Aβ levels, and enhance synaptic plasticity (42). Musk ketone molecules are responsible for the main physiological activity of musk, which can not only resist dementia and fight against cerebral ischemia, but also has low cytotoxicity and a variety of potential health benefits, such as anti-tumor effects, beneficial effects on ischemic heart disease, and the inhibition of diabetic peripheral neuropathy (38,43,44). These effects will help promote cell proliferation and angiogenesis, reduce apoptosis and inflammation, and maintain cell viability, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al (2012) and Zhang et al (2020) reported that muscone can inhibit apoptosis via inhibiting expression of caspase 8 and Fas in the cortex and stimulate neural stem cells proliferation transforming them into neurons in ischemia/reperfusion rats. Muscone has also been suggested to mitigate hyperglycemia-induced Schwann cell autophagy and apoptosis partially by activating the Akt/mTOR signaling pathway (Dong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, musk also inhibited the activity of hydatid cyst [ 113 ]. Dong et al demonstrated that muscone (0.1, 1, 10, 50 mol/L) could reduce high glucose-induced autophagy and apoptosis in RSC 96 cells, and its mechanism was to activate the AKT/mTOR signaling pathway [ 26 ].…”
Section: Pharmacological Effectsmentioning
confidence: 99%